The use of nutritional blocks as a tool for grazing management in extensive sheep husbandry - Ormaechea, Sebastián Gabriel; Cipriotti, Pablo Ariel; Distel, Roberto Alejandro; Peri, Pablo Luis (Asociación Argentina de Ecología, 2021)
The improvement in grazing spatial distribution is an important goal for the efficient and sustainable management of rangelands. However, extensive livestock systems such as the Patagonian rangelands generally fails due to the large paddock size (up to 6000 ha). The purpose of this study was to evaluate the effectiveness of the strategic use of nutritional blocks as an atractive element in underused areas of the landscape, in a shrub steppe of low cover (less than 50%) under dry climate. The spatial distribution of sheep was evaluated in two extensive paddocks (1900 and 5500 ha) under two sequential treatments (With nutritional blocks and Traditional management without nutritional blocks) in two years. The study was carried out using wethers of the Corriedale breed, with an average stocking rate of 0.17±0.03 sheep/ha. The geotracking of wethers was obtained by means of collars equipped with global positioning system technology, configured with a measuring frequency of 5 minutes within an average period of 15 days. The use of nutritional blocks resulted in a 46.1-57.4% expansion in the daily home range with respect to the traditional management, suggesting a more spatial homogeneous use of the paddocks by sheep. These results would have important practical implications, considering that the use of nutritional blocks would allow the combination of supplementation strategies with the sustainable use of pastoral resources.